Frequency Division Based Coordinated Control of Three-Port Converter Interfaced Hybrid Energy Storage Systems in Autonomous DC Microgrids - Panbao Wang; Xiaonan Lu; Wei Wang; Dianguo Xu (IEEE Access, 2018)
DC microgrids (MGs) feature remarkable advantages of integrating renewable energy sources and loads with DC coupling. In order to improve the operation performance of a dc MG in both steady and transient states, in this paper a hybrid energy storage system (HESS) interfaced by a three-port converter (TPC) is studied. Particularly, a battery and an ultra-capacitor (UC), which form the HESS, are connected at the source side of the TPC, respectively. Aiming at a phase-shifting controlled full-bridge isolated TPC, in addition to conventional droop control loop, a frequency division-based control method is proposed to achieve rational power sharing between the battery and UC. Due to the characteristics of TPC, virtual inductance and virtual capacitance loops are implemented using the input currents at the battery and UC ports. The frequency division between the battery and UC in the HESS is quantitatively analyzed by using the frequency domain small-signal analysis considering the characteristics of power exchange in the phase-shifting controlled TPC. A simulation model built in MATLAB/Simulink and a prototype comprised of a battery, a UC, a programmable dc load, and auxiliary components are implemented to validate the proposed TPC-interfaced HESS under different operation scenarios.